Decoding the Rise of China Taiwanese and Japanese Perspectives (Springer Singapore, 2018)
This edited collection provides a synthetic analysis of the rise of contemporary China and its impact on the current global system from a range of Asian and Western perspectives. Highlighting Taiwanese and Japanese viewpoints, the book considers a macro, integrated vision of the rise of China and examines the vital cultural factors which link domestic politics and foreign policy in the Sino-Japanese relationship. The book addresses key policy matters, such as the internationalization of the Chinese currency and Arctic diplomacy, and provides a key reference on contemporary Chinese foreign policy and the Sino-Japanese relationship for students, academics experts and policy makers in the field of Area Studies, History and International Relations.